MYTHOLOGICAL IMAGES REPRESENTING THEONYMIC CONCEPTS (Scientific journal of the Fergana State University, 2024)
As you know, the Creator is beautiful, he is a lomacon in the place. In folk art and classical literature, he is characterized by a variety of beautiful appearances. The article discusses the concept of creator of a beautiful mythological image — pеri.